(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Cuong LCV, Souvannalath B, Ha TP, Lien LQ, Tam VTT, Hoai PTT, Anh HLT, Dat TTH. 2022. Isolation and screening of entomopathogenic fungi against the grasshopper Oxya chinensis (Orthoptera: Acrididae) from rice fields in Thua Thien Hue, Vietnam. Biodiversitas 23: 4906-4911. The grasshopper Oxya chinensis is one of the most abundant herbivorous insects of rice plants in Vietnam and causes severe damage to the crop. Therefore, biological control has become a particularly valuable method for grasshopper and insect control in agricultural production. The aim of the present study was to isolate and investigate the potential entomopathogenic fungi against the grasshopper O. chinensis from rice fields in Thua Thien Hue, to develop environmentally friendly bio-insecticides. The results showed that 37 fungal isolates were isolated from dead grasshoppers collected from rice fields in Thua Thien Hue province. Results of pathogenicity screening of 12 selected fungal isolates showed that the mortality rate of 4th-instar grasshopper nymphs O. chinensis ranged from 21.99% to 100% after 15 treatment days at a concentration of 1 × 108 conidia/ml. Of these, three fungal isolates, namely NL3, NL4, NL12 showed the highest pathogenicity against the grasshopper O. chinensis with mortality rates of 87.73%, 89.81%, and 100%, respectively after 15 days. LC50 values of NL3, NL4, NL12 isolates against 4th-instar nymphs and adults of O. chinensis ranged from 9.5×104 to 4.8×105 conidia/mL and 7.8 × 106 to 2.5 × 106 conidia/mL, respectively at 7 days. LT50 values of NL3, NL4, NL12 isolates against 4th-instar nymphs and adults of O. chinensis were from 4.1 to 4.9 days and 5.5 to 6.1 days, respectively at a concentration of 1 × 108 conidia/mL. Results from morphological identification and nuclear ribosomal internal transcribed spacer (ITS) gene sequence showed that three potential entomopathogenic fungi were Aspergillus tamarii, Beauveria bassiana, and Metarhizium anisopliae. The pathogenicity of Aspergillus tamarii, Beauveria bassiana, and Metarhizium anisopliae against the grasshopper O. chinensis is reported for the first time. The present investigation revealed that these entomopathogenic fungi could be a useful source for developing environment-friendly bio-insecticides for sustainable agricultural production.